2022
DOI: 10.1007/s00705-022-05496-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of chicken bursae of Fabricius miRNAs in response to very virulent infectious bursal disease virus

Abstract: Infectious bursal disease virus (IBDV) can cause a highly contagious immunosuppressive disease in young chickens, resulting in considerable economic losses to the poultry industry. MicroRNAs (miRNAs) are crucial regulators of gene expression and are involved in the pathogenesis of IBDV infection. To investigate the roles of miRNA in chicken bursae of Fabricius in response to very virulent IBDV (vvIBDV) infection, RNA sequencing was performed. For this, we established an IBDV infection model as observed using h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In contrast, miR-3536 expression was significantly higher in Marek's disease virus-transformed T cell lines compared to control lines [34]. Expression of miR-3536 was strongly upregulated in bursae of Fabricius of chickens infected with very virulent infectious bursal disease virus [35].…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, miR-3536 expression was significantly higher in Marek's disease virus-transformed T cell lines compared to control lines [34]. Expression of miR-3536 was strongly upregulated in bursae of Fabricius of chickens infected with very virulent infectious bursal disease virus [35].…”
Section: Discussionmentioning
confidence: 83%
“…In a recent study, it was found that a total of 1710 miRNAs were identified in vvIBDV-infected BF tissues and mock-infected controls, and there were 42 miRNAs with upregulated expression and 35 miRNAs with downregulated expression. miR-1684b-3p, gga-miR-1788-3p, and gga-miR-3530-5p had especially significantly varied expression levels following IBDV infection, with their potential target genes, including THBS1, STAT1, STAT3, and MYD88 [ 117 ]. These predicted results suggest that these gga-miRs might play a role in apoptosis, inflammation, and the IFN response, but further evidence will be required to determine the exact role of these miRNAs in the host response to IBDV infection.…”
Section: Host Response To Ibdv Infection At the Rna Levelmentioning
confidence: 99%
“…For example, the lncRNA CHRF can bind miR-489 to regulate cardiac hypertrophy [ 35 ]. A number of studies have indicated that a single lncRNA or miRNA can effectively affect IBDV replication by regulating key gene expression in the IFN-I or JAK-STAT signalling pathways [ 27 , 33 , 36 , 37 ]. However, it is not yet clear whether lncRNAs are involved in the pathogenesis of IBDV infection, serving as ceRNAs.…”
Section: Introductionmentioning
confidence: 99%